(untitled) (Revista Argentina de Musicología, 2019)
In this paper, the figure of the conductor and composer Lorenzo Barbero, one of the most iconic references of tango in Córdoba in the first half of the twentieth century, who displays a trajectory of more than sixty years and a prolific production, is addressed. We contextualize his works within the concepts of “argentinidad”, “provinciano”, and “porteño”, taking into account clashing and cooperative perspectives. Furthermore, we work with musical references from his own production: in compositions of his own authorship as well as in other pieces that were part of the repertoire of his "Orquesta de la Argentinidad", between 1950 and 1954. The aim of this paper is to expose the dialectic of elements inherent in folklore and tango within musical discourse. Finally, we want to elucidate whether there is concordance among the expressive universes, both poetic and musical, from this same perspective.